4-Aminoquinoline Based Molecular Hybrids as Antimalarials: An Overview - Manohar, Sunny; Tripathi, Mohit; S. Rawat, Diwan (Current Topics in Medicinal Chemistry, 2014)
In recent times, the novel concept of generating hybrid molecules by pharmacophoric hybridisation approach is fast becoming an alternative to other existing strategies of drug development. These hybrids also known as ‘dual drugs’ or ‘double drugs’ are especially found to be effective in overcoming drug resistance problems. Towards this end, a lot of effort has been put for generating 4-aminoquinoline based hybrid molecules as next generation antimalarial drugs effective in malarial chemotherapy. This short review deals about the recent advances carried in the field of 4-aminoquinoline based molecular hybrids as potential antimalarial agents. It also presents a brief and simplified story on the development of 4-aminoquinolines as a mainstay in malarial research programmes.
Keywords: hybrid